Formulation and In vitro Evaluation of Unfolding Type Expandable Gastroretentive Film of Enalapril Maleate - Ullah, Md Bashir; Karim, Md Rezaul; Alam, Md Shamsul; Hassan, Md Rajib; Bhuiyan, Mohiuddin Ahmed; Rana, Md Sohel (Bangladesh Pharmaceutical Journal, 2018)
The present work was based on the development and characterization of unfolding type gastroretentive dosage form appropriate for controlled release of enalapril maleate. Drug loaded films were prepared by solid dispersion technique using methocel K15 and eudragit RSPO and eudragit RLPO as polymers and polyethylene glycol 400 (PEG 400) as the plasticizer. The film folded in a capsule shell was shown to unfold in the gastric juice and provide drug release up to 12 h in the acidic medium. Formulations provided satisfactory unfolding characteristics allowing expansion to remain in the stomach. Formulation containing above 60% content of eudragit RSPO and eudgrait RLPO combination of total polymer content provided satisfactory film integrity over 12 hours. The result revealed that formulation F1 showed a minimum percentage of drug release of 63.41% followed by formulation F2, F3, F4 and F5 with 66.76%, 80.21%, 83.26% and 86.92% release in 8 hour respectively. Formulation with high proportion of eudragit RLPO and RSPO combination in total polymer content was found to be slow in drug release and lower the release from the polymeric film over time. As the concentration of HPMC K 15 in total polymer content increased the release rate of enalapril maleate as well as % release from the polymeric film also increased over time. Most of the formulation followed Higuchi release kinetics followed by Korsmeyer release kinetics. The drug release mechanism from the film follows Fickian and Non Fickian release kinetics. The films were evaluated for mechanical properties, in vitro drug release and unfolding behavior based on the mechanical shape memory of polymers. Absence of drug polymer interaction and uniform drug dispersion in the polymeric layers was revealed by DSC, FT-IR and SEM studies. Bangladesh Pharmaceutical Journal 20(2): 148-154, 2017